2016
DOI: 10.1016/j.neuroimage.2015.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Application of neurite orientation dispersion and density imaging (NODDI) to a tau pathology model of Alzheimer's disease

Abstract: Increased hyperphosphorylated tau and the formation of intracellular neurofibrillary tangles are associated with the loss of neurons and cognitive decline in Alzheimer's disease, and related neurodegenerative conditions. We applied two diffusion models, diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), to in vivo diffusion magnetic resonance images (dMRI) of a mouse model of human tauopathy (rTg4510) at 8.5 months of age. In grey matter regions with the highest degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 31 publications
(45 reference statements)
9
154
0
Order By: Relevance
“…NODDI indices derived from the biophysical model may be more sensitive than FA. This is consistent with several other studies showing the greater potential of NODDI parameters than FA, including direct comparison studies in human spinal cord with MS, mouse corpus callosum, and mouse model of human Alzheimer's disease . However, at least one study reported the opposite, the insensitivity of NODDI compared to DTI measures including FA .…”
Section: Discussionsupporting
confidence: 91%
“…NODDI indices derived from the biophysical model may be more sensitive than FA. This is consistent with several other studies showing the greater potential of NODDI parameters than FA, including direct comparison studies in human spinal cord with MS, mouse corpus callosum, and mouse model of human Alzheimer's disease . However, at least one study reported the opposite, the insensitivity of NODDI compared to DTI measures including FA .…”
Section: Discussionsupporting
confidence: 91%
“…Whereas there is evidence that MD is also more sensitive to age than FA among those with mild stroke48, our sample composition has implications for another aspect of our results. Whereas hippocampal volume and ICVF did not appear to provide unique information about age in this sample, both ICVF (rather than FA)49 and hippocampal volume50 are important dementia biomarkers, emphasizing that our findings, which focus on normal ageing, cannot necessarily be generalized to clinical populations.…”
Section: Discussionmentioning
confidence: 54%
“…Neurite orientation-dispersion and density imaging (NODDI) is a recently introduced biophysical diffusion modeling approach that approximates neurites (i.e., axons and dendrites) as a set of sticks with zero radii to capture the extremely restricted diffusion perpendicular to the neurites and unhindered diffusion along them (15). Thus, NODDI is well suited for microstructural modeling of GM tissue, which is primarily composed of dendritic trees and crossing axons, as it permits high dispersion of the neuritic orientations (15,18). This technique characterizes: the spatial configuration of the neurites with the orientation dispersion index (ODI); and tissue microstructural composition with the neuritic density index (NDI), the volume fraction of neurites in brain tissue (15).…”
Section: Introductionmentioning
confidence: 99%